2017
DOI: 10.3184/175815617x14967389842918
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Observations of the Digestive Canal of the Great Bustard (Otis Tarda)

Abstract: This study focussed on the microstructure of the digestive canal of the Great Bustard ( Otis tarda). Under scanning electron microscopy (SEM), different morphological plicae (rounded protrusions about 10 μm in height) were observed at different locations along the inner surface of the oesophagus. Concentrated microvilli can be seen on the surface of the protrusions in high-power fields. There are papillae in the mucosal fold on the inner surface of the glandular stomach, with openings of about 250 μm in diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Gut microbial diversity was found to remain positively correlated with the gut retention time of the host. In addition, the Great Bustard, Common Crane, and Common Coot all have well-developed ceca, which increases the retention time of food in the gut and promotes the stability of gut symbionts ( Fanke et al, 2011 ; Crompton and Nesheim, 2016 ; Li et al, 2017 ). Via PCoA analysis coupled with ANOSIM statistical test, we consistently revealed that these three sympatric wild birds have significantly different gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbial diversity was found to remain positively correlated with the gut retention time of the host. In addition, the Great Bustard, Common Crane, and Common Coot all have well-developed ceca, which increases the retention time of food in the gut and promotes the stability of gut symbionts ( Fanke et al, 2011 ; Crompton and Nesheim, 2016 ; Li et al, 2017 ). Via PCoA analysis coupled with ANOSIM statistical test, we consistently revealed that these three sympatric wild birds have significantly different gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…During wintering, the Great Bustard, Common Coot, and Common Crane share the same habitat and feed mainly on plant seeds from farmlands and wastelands ( Johnsgard, 1983 ; Mouronval et al, 2007 ; Liu et al, 2018 ). These species all have a complex digestive system with a developed cecum ( Fanke et al, 2011 ; Crompton and Nesheim, 2016 ; Li et al, 2017 ) and share similar behavioral patterns, such as terrestrial living and group-living ( Alonso et al, 2004 ; Mouronval et al, 2007 ; Lu et al, 2021a ). Simplification of confounding factors can facilitate comparative analysis of the gut microbiota of wild bird species living under natural conditions ( Lee et al, 2020 ), and a shared overwintering habitat provides an ideal condition to compare the adaptive changes in the gut microbiota of different hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbial diversity was found to remain positively correlated with the gut retention time of the host. In addition, the Great Bustard, Common Crane, and Common Coot all have welldeveloped ceca, which increases the retention time of food in the gut and promotes the stability of gut symbionts (Fanke et al, 2011;Crompton and Nesheim, 2016;Li et al, 2017). Via PCoA analysis coupled with ANOSIM statistical test, we consistently revealed that these three sympatric wild birds have significantly different gut microbiota.…”
Section: Discussionmentioning
confidence: 71%
“…During wintering, the Great Bustard, Common Coot, and Common Crane share the same habitat and feed mainly on plant seeds from farmlands and wastelands (Johnsgard, 1983;Mouronval et al, 2007;Liu et al, 2018). These species all have a complex digestive system with a developed cecum (Fanke et al, 2011;Crompton and Nesheim, 2016;Li et al, 2017) and share similar behavioral patterns, such as terrestrial living and group-living (Alonso et al, 2004;Mouronval et al, 2007;Lu et al, 2021a). Simplification of confounding factors can facilitate comparative analysis of the gut microbiota of wild bird species living under natural conditions (Lee et al, 2020), and a shared overwintering habitat provides an ideal condition to compare the adaptive changes in the gut microbiota of different hosts.…”
Section: Introductionmentioning
confidence: 99%